Sex‐Based Differences in Outcomes After Percutaneous Coronary Intervention for Acute Myocardial Infarction: A Report From TRANSLATE‐ACS. Issue 1 (7th February 2014) - Hess, Connie N.; McCoy, Lisa A.; Duggirala, Hesha J.; Tavris, Dale R.; O'Callaghan, Kathryn; Douglas, Pamela S.; Peterson, Eric D.; Wang, Tracy Y.
Abstract : Background: Data regarding sex‐based outcomes after percutaneous coronary intervention (PCI) for myocardial infarction are mixed. We sought to examine whether sex differences in outcomes exist in contemporary practice. Methods and Results: We examined acute myocardial infarction patients undergoing PCI between April 2010 and October 2012 at 210 US hospitals participating in the Treatment with Adenosine Diphosphate Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events after Acute Coronary Syndrome (TRANSLATE‐ACS) observational study. Outcomes included 1‐year risk of major adverse cardiac events and bleeding according to Global Utilization of Strategies To Open Occluded Arteries (GUSTO) and Bleeding Academic Research Consortium (BARC) definitions. Among 6218 patients, 27.5% (n=1712) were female. Compared with men, women were older, had more comorbidities, and had lower functional status. Use of multivessel PCI and drug‐eluting stents was similar between sexes, while women received less prasugrel. Unadjusted cumulative incidence of 1‐year major adverse cardiac events was higher for women than for men (15.7% versus 13.6%, P =0.02), but female sex was no longer associated with higher incidence of major adverse cardiac events after multivariable adjustment (hazard ratio 0.98, 95% CI 0.83 to 1.15). Female sex was associated with higher risks of post‐PCI GUSTO bleeding (9.1% versus 5.7%, P <0.0001) and postdischarge BARC bleeding (39.6% versus 27.9%, P <0.0001). Differences persisted after adjustment (GUSTO: hazard ratio 1.32, 95% CI 1.06 to 1.64; BARC: incidence rate ratio 1.42, 95% CI 1.27 to 1.56). Conclusions: Female and male myocardial infarction patients undergoing PCI differ regarding demographic, clinical, and treatment profiles. These differences appear to explain the higher observed major adverse cardiac event rate but not higher adjusted bleeding risk for women versus men.